2004
DOI: 10.1002/eji.200324717
|View full text |Cite|
|
Sign up to set email alerts
|

Maintenance of memory CTL responses by T helper cells and CD40‐CD40 ligand: antibodies provide the key

Abstract: Cytotoxic T lymphocytes (CTL) are essential for control of primary infections by many pathogens and in particular by non-cytopathic viruses. It has been proposed that long-term maintenance of CTL memory and control of lymphocytic choriomeningitis virus (LCMV) is dependent upon the presence of T helper cells and interaction of antigen-presenting cells and CTL via CD40 and its ligand CD40L. However, we demonstrate here that CD40-CD40L interaction maintains CTL memory by induction of virus-specific antibodies. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Moreover, observations that patients with Bruton's agammaglobulinemia can control acute viral diseases [22] helped create a generally held notion that, unlike what applies for protection against reinfection, primary viral infections were predominantly controlled by cell-mediated immunity [22]. Experiments in mice, monkeys, and man had shown that passive administration of potent nAbs or transgenic expression of a virus-neutralizing B cell receptor (BCR) can prevent infection [23,24], augment virus control during infection [2527], or prevent the establishment of persistence [28,29]. Still, these experimental observations did not challenge the above dogma since the experimental conditions chosen did not mimic the kinetics and magnitude of the host's spontaneous nAb response (delayed and weak).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, observations that patients with Bruton's agammaglobulinemia can control acute viral diseases [22] helped create a generally held notion that, unlike what applies for protection against reinfection, primary viral infections were predominantly controlled by cell-mediated immunity [22]. Experiments in mice, monkeys, and man had shown that passive administration of potent nAbs or transgenic expression of a virus-neutralizing B cell receptor (BCR) can prevent infection [23,24], augment virus control during infection [2527], or prevent the establishment of persistence [28,29]. Still, these experimental observations did not challenge the above dogma since the experimental conditions chosen did not mimic the kinetics and magnitude of the host's spontaneous nAb response (delayed and weak).…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that CD4 + T cells are required after the priming and expansion phase (i.e., during the contraction phase) and that this help can be antigen non-specific 60 . CD4 + T cell help following LCMV infection is independent of CD40-mediated licensing of DCs or CD8 + T cells, with passive transfer of LCMV-specific antibodies sufficient to restore a protective memory CD8 + T cell response in the absence of CD40-CD40L interactions through the facilitation of viral clearance 62,63 . “Helpless” CD8 + T cells displayed increased expression of T-bet, a transcription factor involved in fine-tuning CD8 + effector and memory T cell differentiation, with reduction of T-bet expression restoring the functionality of these cells 64,65 .…”
Section: Cd4+ T Cell Help Following Systemic Infectionmentioning
confidence: 99%
“…But limited researches were reported on the genetic factors which influence the genesis of asymptomatic chronic HBV infections. Previous studies have demonstrated that activation of CD40 signaling is indispensable for the induction of effective virus-specific CD8+ T-cell responses, which is required for the virus clearance [30,31]. Using a transgenic mouse model, Chisari et al showed that the HBV antigen-specific CD8+ T cell exhaustion was able to be rescued by CD40-mediated mDC activation [32].…”
Section: Discussionmentioning
confidence: 99%